Rift Valley Fever Outbreak Investigation Associated with a Dairy Farm Abortion Storm, Mbarara District, Western Uganda, 2023 - Luke Nyakarahuka; Shannon Whitmer; Sophia Mulei; Joanita Mutesi; Jimmy Baluku; Jackson Kyondo; AmyWhitesell; Carson Telford; Alex Tumusiime; Calvin Richie Torach; Dianah Namanya; Mariam Nambuya; et al. (Viruses, 2025)
In Africa, Rift Valley Fever poses a substantial risk to animal health, and human cases occur after contact with infected animals or their tissues. RVF has re-emerged in Uganda after nearly five decades, with multiple outbreaks recorded since 2016. We investigated a unique RVF outbreak associated with an animal abortion storm of 30 events and human cases on a dairy farm in Mbarara District, Western Uganda, in February 2023. Genomic analysis was performed, comparing animal and human RVF viruses (RVFV) circulating in the region. Acluster of thirteen human RVF cases and nine PCR-positive animals could directly be linked with the abortion storm. Overall, during the year 2023, we confirmed 61 human RVFVcases across Uganda, 88.5% of which were reported to have had direct contact with livestock, and a high case fatality rate of 31%. We recommend implementing extensive health education programs in affected communities and using sustainable mosquito control strategies to limit transmission in livestock, coupled with initiating animal vaccination trials in Uganda.
Keywords: Rift Valley Fever; Zoonotic transmission; Animal abortion storms; Human RVF outbreaks; Western Uganda; Livestock–human interface; RVF virus; Vaccination trials